Examination and treatment of unilateral spatial neglect using virtual reality in three-dimensional space. Issue 6 (2nd November 2021) - Numao, Taku; Amimoto, Kazu; Shimada, Tomoko
ABSTRACT: Here, we developed a method that randomly generates balloons in the left-right, up-down, and near-far spaces on a monitor using a head-mounted display. In this study, we evaluated a lack of stimulus-driven attention case that was undetected by conventional assessments such as the Behavioral Inattention Test. We could identify mild neglect with our virtual reality method, as later confirmed using the Catherine Bergego scale. After repeated practice under a tilted background space condition, the patient demonstrated a reduction in the time needed to perceive the appearing balloons, suggesting a therapeutic effect.